PENGUKURAN RASIO KEUANGAN TERHADAP KINERJA BANK PEMERINTAH Di INDONESIA - Panggabean, Priska Basariana (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2023)
Banking financial performance is calculated based on financial ratios, which will show the bank's ability to comply with established regulations and financial systems and the amount of profit generated from the use of banking capital. The financial ratios that are calculated and analyzed in this study are CAR, NIM and LDR as independent variables, and how these ratios affect the bank's ability to manage capital over invested assets, namely ROA as a dependent variable. The study used financial statement data of state banks in Indonesia with a research period of 5 years and was analyzed using simultaneous regression method. From the tests conducted, it is known that NIM and LDR are positively correlated with ROA and CAR is negatively correlated with ROA. This shows that the bank's ability to manage assets, disburse credit for deposits obtained from the public, as well as the ability to allocate a certain amount of capital in accordance with central bank regulations, will affect the rate of return on all management of productive assets of the bank.